1994
DOI: 10.1007/bf00188673
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging or metaiodobenzylguanidine scintigraphy for the demonstration of paragangliomas?

Abstract: Paragangliomas are tumours arising from paraganglionic tissue dispersed from the base of the skull to the pelvic diaphragm. These tumours produce symptoms by secreting catecholamines (functioning tumours) or by local tumour expansion. They can be part of several hereditary disorders. The introduction of magnetic resonance (MR) imaging and metaiodobenzylguanidine (MIBG) scintigraphy has provided new insights into paragangliomas and has tremendously changed the topographic diagnosis of paragangliomas. Both techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
5

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 63 publications
0
17
0
5
Order By: Relevance
“…CT or MRI represent the first diagnostic step in the localization of phaeochromocytoma (Van Gils et al 1994), but frequently the nature of the identified adrenal mass remains to be clarified (Berglund et al 2001). Furthermore, the functional meaning of suspected paragangliomas or metastatic malignant masses can be difficult to obtain with CT or MRI and it has been demonstrated that when postoperative changes are present (Pacak et al 2001) the sensitivity of both MRI and CT decreases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CT or MRI represent the first diagnostic step in the localization of phaeochromocytoma (Van Gils et al 1994), but frequently the nature of the identified adrenal mass remains to be clarified (Berglund et al 2001). Furthermore, the functional meaning of suspected paragangliomas or metastatic malignant masses can be difficult to obtain with CT or MRI and it has been demonstrated that when postoperative changes are present (Pacak et al 2001) the sensitivity of both MRI and CT decreases.…”
Section: Discussionmentioning
confidence: 99%
“…In this group of patients, it is worth noticing how functional data may be useful in distinguishing between a normal adrenal and a pheochomocytoma. Many studies have compared the accuracy of CT, MRI and 131 I-MIBG scintigraphy in the diagnosis of suspected pheochromocytomas (Maurea et al 1993, 1996, Van Gils et al 1994, Elgazzar et al 1995, Freitas 1995. Others have reported results with 123 I-MIBG, which enjoys the advantages of having an energy more suitable for the g camera, a shorter half-life than 131 I and the absence of b emission (Maurea et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of morphological [computed tomography, magnetic resonance imaging (MRI)] and metabolic methods [metaiodobenzylguanidine (MIBG) scintigraphy, somatostatin receptor scintigraphy] have been used for diagnostic imaging of glomus tumours [9,10,11,12,13,14,15,16]. A metabolic method that has not been described thus far is 18 F-DOPA whole-body positron emission tomography (PET).…”
Section: Introductionmentioning
confidence: 99%
“…According to WHO classification all tumors of the paraganglion system are called paraganglioma. Paragangliomas occurring in the head and neck region (from the carotid and vagal body, from the glomus jugulare and glomus tympanicum) are called chemodectomas or glomus tumors [1,2]. They are in general rare, solitary and slow growing tumors of neuroendocrine origin [3].…”
mentioning
confidence: 99%